Functional usability analysis of top Korean mobile role playing games based on user interface design - Seunh Hoon Lee; Doo Heon Song (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Mobile Tole Playing Games (RPGs) are now very popular in gaming market. Still, we have great constraint in hardware provided such as screen size and interaction speed. Adopting techniques such as auto play enables the game designers to weaken the burdens of porting RPG scales to mobile platform. However, the interface design in mobile platform becomes quite different from PC based platform. In this paper, we investigate how user interface functionalities are provided for popular mobile RPGs based on google play downloaded between the year of 2014 and 2016. We analyze the commonalities and the differences of recent successful mobile RPGs first and take a user survey with heuristics. In result, subjects who are 16 ~ 25 in age weakly accept current interface layout and control as over 70% positive rate in 4 point Likert scale test.